2012
DOI: 10.1124/mol.112.081364
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin A Inhibits Myeloid Cell Leukemia-1 to Induce Apoptosis in Oral Squamous Cell Carcinomas and Tumor Xenograft through Activation of Bax and Oligomerization

Abstract: In several human malignancies, overexpression of myeloid cell leukemia-1 (Mcl-1) confers resistance to induction of apoptosis; however, Mcl-1-mediated inhibition of apoptosis in oral squamous cell carcinoma (OSCC) is not fully understood and has been investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…Though it shows potential to treat neurodegenerative diseases such as Huntington’s Disease [1], Alzheimer’s, and Parkinson’s, it has primarily been investigated as an anticancer drug. Mithramycin has been used clinically against testicular cancer [2] and leukemia [3], and preclinical studies have shown activity against glioma [4], pancreatic cancer [5], prostate cancer [6], oral squamous cell carcinoma [7], and lung and esophageal cancer [8]. Patients receiving mithramycin often develop hepatotoxicity [9]; various analogs have been developed in an attempt to curtail dose-limiting side effects [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Though it shows potential to treat neurodegenerative diseases such as Huntington’s Disease [1], Alzheimer’s, and Parkinson’s, it has primarily been investigated as an anticancer drug. Mithramycin has been used clinically against testicular cancer [2] and leukemia [3], and preclinical studies have shown activity against glioma [4], pancreatic cancer [5], prostate cancer [6], oral squamous cell carcinoma [7], and lung and esophageal cancer [8]. Patients receiving mithramycin often develop hepatotoxicity [9]; various analogs have been developed in an attempt to curtail dose-limiting side effects [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Mcl-1 has been reported to be a critical survival-promoting molecule in hematopoietic cells, and its overexpression is known to be associated with a variety of human hematopoietic and lymphoid cancers (22). The anti-apoptotic splice variant of Mcl-1 was also augmented in human oral cancer (23), and our previous study demonstrated that the overexpression of Mcl-1 may be strongly correlated with oral cancer development (24).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported a high expression level of Mcl-1 in tumor cells of human primary squamous cell carcinoma (SCC) and SCC cell lines (24,26). It has been demonstrated that the blockage of its function may play a potentially critical and novel role by the use of either specific siRNA or inhibitor in the treatment of SCC (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cytokines and pathways closely associated with OSCC include cyclooxygenase-2 (Chan et al, 1999), myeloid cell leukemia-1 (Shin et al, 2013), serine/threonine kinase signaling pathway (Gao et al, 2013) and PD-1/PD-L1 (the inhibitory receptor Programmed Death-1/Programmed cell death ligand 1) pathway (Lyford-Pike et al, 2013).…”
Section: Bioinformatics Analysis Reveals Significant Genes and Pathwamentioning
confidence: 99%